Examine the Treatment Outcomes of Severe Acute Malnutrition in Pediatric Population by Using Formula F100 Therapeutic Feed (Medical Forum Monthly, 2024)
Objective: To examine the prevalence and treatment outcomes of severe acute malnutrition in children.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Department of Pediatric Medicine Unit-3, Civil Sandeman Provincial Hospital Quetta from January 2019 to June 2019.Materials and Methods: A total of 150 patients of both genders presented with severe acute malnutrition were included in this study. Patient’s ages were ranging from 2 months to 48 months. Patients demographic including age, sex, malnutrition type and residence were recorded after taking informed consent from patient’s parents/guardians. Presentations on admission were recorded. F75 and F100 therapeutic feed were given to all the patients (WHO Guideline for malnutrition). Outcomes were recorded.Results: There were 80 (53.33%) male patients while 70 (46.67%) were females. Sixty eight (45.33%) patients were ages less than 10 months and 82 (54.67% were ages above 10 months. From all the patients 134 (89.33%) patients were marasmus and 16 (10.67%) patients were khwashikor. Mean weight gain by using F100 was 7.26+3.45 gm/kg/day. 92% patients were recovered and 8% died during treatment. The most common presentation was diarrhea.Conclusion: The use of F75 and F100 therapeutic feed for the treatment of severe acute malnutrition were very effective with low rate of mortality.